Immunogenicity and predictive factors of hepatitis B vaccination with Fendrix® in chronic kidney disease patients - Cristina Hernán-García; Cristina Hernán-García; Daniel Leonardo Sánchez-Carmona; Lucía Czestochowa Mateo-Otero; Virginia Fernández-Espinilla; Virginia Fernández-Espinilla; Paula Andrea Rodriguez-Ducuara; José Javier Castrodeza-Sanz; José Javier Castrodeza-Sanz; Camino Prada-García; Camino Prada-García (Frontiers in Public Health)
Hepatitis B virus (HBV) infection and chronic kidney disease (CKD) pose major global health challenges. CKD patients face a heightened risk of HBV infection, worsening their prognosis. This study evaluated the immune response to hepatitis B vaccination in CKD patients, the persistence of antibodies, and factors influencing vaccine efficacy. A retrospective study was conducted on 173 CKD patients (2014–2019) receiving routine vaccination at the Hospital Clínico Universitario de Valladolid, Spain. (ZIP Code:47003) Patients were immunized with Fendrix® on a 0-1-2-6-month schedule, and verbal informed consent was obtained. A protective response was defined as Anti-HBs >10 IU/L, and a robust response as >100 IU/L. Overall, 90.8% achieved a protective response. Age was not a significant predictor (p = 0.137) between non-responders and protective or robust responders. 32.95% of patients died during follow-up. A robust response at the end of vaccination cycle was associated with higher antibody titers at 12 months (p = 0.002) but not at 24 (p = 0.550) or 36 months (p = 0.739). Kaplan–Meier analysis estimated median antibody duration as 26.5 months (Anti-HBs > 10 IU/L) and 25.4 months (Anti-HBs > 100 IU/L). A delay in vaccination compared to the recommended schedule was observed (one-sample Wilcoxon test, p < 0.001). Fendrix® effectively induces protective immunity in CKD patients, but a robust early response does not ensure long-term persistence. The decline in antibody levels suggests the need for booster doses and periodic antibody monitoring to optimize long-term protection. Suboptimal vaccination adherence may reflect the inherent complexities of real-world clinical practice.